1986
DOI: 10.1002/ajmg.1320250303
|View full text |Cite
|
Sign up to set email alerts
|

New multiple congenital anomalies/mental retardation syndrome with cardio‐facio‐cutaneous involvement—the CFC syndrome

Abstract: Eight patients (4 males, 4 females) were affected with a previously undefined multiple congenital anomalies/mental retardation syndrome which was designated the Cardio-Facio-Cutaneous (CFC) syndrome and which includes congenital heart defects, characteristic facial appearance, ectodermal abnormalities, and growth failure. Cardiac defects were variable, the most common being pulmonic stenosis and atrial septal defect. Typical facial characteristics were high forehead with bitemporal constriction, hypoplasia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
197
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(200 citation statements)
references
References 8 publications
1
197
0
2
Order By: Relevance
“…16 Because of the overlapping clinical features there is an ongoing discussion whether CFC syndrome and NS are allelic, or whether CFC is a contiguous gene syndrome. 17,18 Although two patients with CFC were reported to have an interstitial deletion of 12q21-22, 19,20 no deletions could be found in a further seven CFC patients investigated by Zollino et al, 21 using the same probe employed by Rauen et al 19 Familial occurrence has been reported in two families.…”
Section: Noonan-ptpn11 L Musante Et Al 204mentioning
confidence: 99%
“…16 Because of the overlapping clinical features there is an ongoing discussion whether CFC syndrome and NS are allelic, or whether CFC is a contiguous gene syndrome. 17,18 Although two patients with CFC were reported to have an interstitial deletion of 12q21-22, 19,20 no deletions could be found in a further seven CFC patients investigated by Zollino et al, 21 using the same probe employed by Rauen et al 19 Familial occurrence has been reported in two families.…”
Section: Noonan-ptpn11 L Musante Et Al 204mentioning
confidence: 99%
“…In this family some individuals present with NS and features suggestive of CFC 8 and others with NS features only. 3,9 Subjects, material and methods…”
Section: Introductionmentioning
confidence: 78%
“…Patients with CS have increased incidence of rhabdomyosarcoma, transitional cell carcinoma and neuroblastoma (Gripp, 2005); NS patients of rhabdomyosarcoma, juvenile myelomonocytic leukemia and acute lymphoblastic leukemia (Tartaglia and Gelb, 2005) and LS patients of acute myelogenous leukemia and neuroblastoma (Keren et al, 2004;Merks et al, 2005). CFC has not been definitively linked with malignancies although they do appear to have increased incidence of hemangiomatoses at birth (Reynolds et al, 1986). Given the previously described role of MKK signaling in vascular development, it is possible that the increased incidence of malignancies in these patients may be related to altered angioproliferative signaling induced by aberrant MEK 1 or MEK 2 signaling.…”
Section: Mkk Signaling In Developmental Syndromesmentioning
confidence: 99%